Left atrial posterior wall isolation affects complex fractionated atrial electrograms in persistent atrial fibrillation. Issue 3 (12th April 2019) - Nakatani, Yosuke; Sakamoto, Tamotsu; Yamaguchi, Yoshiaki; Tsujino, Yasushi; Kataoka, Naoya; Nishida, Kunihiro; Mizumaki, Koichi; Kinugawa, Koichiro
Abstract: Background: The impact of left atrial posterior wall isolation (LAPWI) on the complex fractionated atrial electrogram (CFAE) is unknown. Methods: CFAE mapping was performed before and after LAPWI in 46 patients with persistent atrial fibrillation (AF). Results: LAPWI decreased both the variable (fractionated index ≤ 120 ms; from 60 ± 4 cm 2 to 50 ± 4 cm 2, P < 0.001) and continuous (fractionated index ≤ 50 ms; from 4.2 ± 1.0 cm 2 to 3.5 ± 0.9 cm 2, P = 0.036) CFAE areas. Especially, the CFAE areas on the bottom and roof walls of the left atrium and on the posterior and bottom walls of the right atrium significantly decreased after LAPWI. The distribution of variable CFAE areas was not different between the AF‐recurrence (n = 9) and AF‐free (n = 37) groups before LAPWI; however, it was larger in the anterior and septal walls of the right atrium in the AF‐recurrence group than in the AF‐free group after LAPWI (anterior wall, 8% ± 2% vs 5% ± 1%, P = 0.048; septal wall, 23% ± 4% vs 16% ± 1%, P = 0.043). The distribution of continuous CFAE areas on the bottom wall of the right atrium was larger in the AF‐recurrence group than in the AF‐free group both before LAPWI (30% ± 20% vs 4% ± 2%, P = 0.008) and after LAPWI (25% ± 25% vs 3% ± 1%, P = 0.027). Conclusions: LAPWI decreased the CFAE areas and affected their distribution, which contributed to AF recurrence.